The Effect of a Speed-Reading Course on Reading Comprehension of Impulsive and Reflective Learners - Gopalan, Aroo (2023)
Reading comprehension is a daunting task for many ESL learners in the context of Malaysia. Also, little attention, if any, has been accorded to how reflectivity and impulsivity affect language learners’ reading comprehension. To solve this problem, this study focused on the effect of an intervention in the form of a speed reading course on the reading comprehension of reflective and impulsive ESL learners at a college in Malaysia. A confirmatory sequence mixed-methods study was designed. Based on the results of the Nelson Denny Reading pretest, selected samples (n=142) were divided into three groups, i.e., one control group and two experimental groups of impulsive and reflective learners. Barrats et al. (1995) impulsivity test and Kember et al. (2000) reflectivity test was used to group the participants into reflective and impulsive learners. Also 18 reading passages were assigned to the participants in 18 sessions of the treatment course. While the control group read the texts at their convenience, the experimental group recorded their reading time in a score sheet. This information and their reading scores were used to check their progress throughout the course. The comparison the pretest and post-test results allowed the researcher to answer the research questions. As the results of the study revealed, while the speed reading course affected the participants’ reading comprehension, impulsivity or reflectivity did not result in any significant differences. The participants’ reading time was significantly decreased; however, no significant difference was observed between the impulsive and the reflective learners in terms of reading time. Also, after interviewing 13 respondents, the qualitative analysis results through Qualitative Content Analysis (QCA) revealed that the respondents noticed increased efficiency and better comprehension, realized reading techniques, gained confidence in speed reading, found reading easier and more joyful. Time management, answering all questions, reading the whole text, and understanding difficult vocabulary items were among the course's challenges. The respondents also suggested strategy instruction, more practice tests, teaching the essay format and group work to be added to the course. This study has pedagogical implications for course designers and language teachers.